Intracranial infection in an adult caused by Mycoplasma hominis, diagnosed using mNGS technology: a case report - Kai-Meng Wang; Na Mu; He-Bo Wang (Frontiers in Medicine, 2025)
Mycoplasma hominis is a rare cause of adult central nervous system infections, posing significant diagnostic challenges due to its fastidious growth requirements and high false-negative rate in conventional cultures. We report a case of Mycoplasma hominis meningoencephalitis in a postpartum female, diagnosed via metagenomic next-generation sequencing (mNGS) of cerebrospinal fluid (CSF). The patient presented with fever, headache, and progressive neurological deficits following a cesarean section. Neuroimaging revealed a subdural hematoma, and CSF analysis demonstrated an inflammatory response. mNGS identified Mycoplasma hominis, prompting targeted antimicrobial therapy with moxifloxacin and doxycycline, which led to significant clinical improvement. This case underscores the utility of mNGS in detecting rare intracranial infections and highlights the critical role of early pathogen identification in optimizing treatment outcomes.